(untitled) (Zia e Tahqeeq, 2025)
"Commonly used urf and routine matters have their own importance in human life. In Islamic jurisprudence, there are many cases in which examples of matter urf based rulings are found. Although the number of juristic orders and issues regarding worship is very limited, the routine habit is given importance in this case. Regarding purification, the commandments about economic, there are so many problems in which routine habit is also considered . In this way there are many examples of routine habit other than worship issues in Islam. The article addresses the same issues. Change is a defined phenomena in human life. Societies change with the passage of time. The world has become a global village due to scientific inventions.Every quality which is liked by reason and which satisfies the conscience is called urf and the action which is done by people perpetually with all the reason and experience and is considered correct naturally is called Urf. Actually every custom is being adopted due to its burning need and Islam is the perfect religion to meet the needs and requirements of the people. An effort has been made to define and explain Urf’ its validity and impact on economy of Islam in the following article. "